Synthetic bone: design by additive manufacturing - Barba, D; Reed, R; Alabort, E (Elsevier, 2019)
A broad range of synthetic trabecular-like metallic lattices are 3D printed, to study the extra design freedom conferred by this new manufacturing process. The aim is to propose new conceptual types of implant structures for superior bio-mechanical matching and osseo-integration: synthetic bone. The target designs are 3D printed in Ti-6Al-4V alloy using a laser-bed process. Systematic evaluation is then carried out: (i) their accuracy is characterised at high spatial resolution using computed X-ray tomography, to assess manufacturing robustness with respect to the original geometrical design intent and (ii) the mechanical properties - stiffness and strength - are experimentally measured, evaluated, and compared. Finally, this new knowledge is synthesised in a conceptual framework to allow the construction of so-called implant design maps, to define the processing conditions of bone tailored substitutes, with focus on spine fusion devices. The design criteria emphasise the bone stiffness-matching, preferred range of pore structure for bone in-growth, manufacturability of the device and choice of inherent materials properties which are needed for durable implants. Examples of the use of such maps are given with focus on spine fusion devices, emphasising the stiffness-matching, osseo-integration properties and choice of inherent materials properties which are needed for durable implants. STATEMENT OF SIGNIFICANCE: We present a conceptual bio-engineering design methodology for new biomedical lattices produced by additive manufacturing, which addresses some of the critical points in currently existing porous implant materials. Amongst others: (i) feasibility and accuracy of manufacturing, (ii) design to the elastic properties of bone, and (iii) sensible pores sizes for osseointegration. This has inspired new and novel geometrical latticed designs which aim at improving the properties of intervertebral fusion devices. In their fundamental form, these structures are here fabricated and tested. When integrated into medical devices, these concepts could offer superior medical outcomes.